2001
DOI: 10.1577/1548-8675(2001)021<0448:eomhoe>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Mechanical Harvesting of Eurasian Watermilfoil on Angling for Bluegills in Fish Lake, Wisconsin

Abstract: We examined changes in angling effort, catch and catch rates, and fishing and natural mortality of bluegills Lepomis macrochirus associated with mechanical plant harvesting in a lake heavily infested with Eurasian watermilfoil Myriophyllum spicatum. In August 1994, 18% of the total plant biomass was removed in a radial pattern of 2‐m‐wide channels in Fish Lake, Dane County, Wisconsin. After the vegetation removal, winter angler hours increased significantly, whereas summer angler hours did not. The number of b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 11 publications
(17 reference statements)
0
6
0
Order By: Relevance
“…However, some of our models did show a significant (negative) relationship with macrophyte cover at lake scale: total fish abundance, roach abundance as well as the abundance and biomass of fish <10 cm. Studies conducted in multiple northern temperate lakes found that excessive plant growth in a lake could reduce fish growth and the abundance of some species (Cheruvelil et al, 2005; Maceina et al, 1991; Unmuth et al, 2001). In addition, our results revealed that the negative relationships between macrophytes and total fish abundance as well as the abundance and biomass of fish <10 cm were strongly associated with lakes with high plant cover, as shown by the within‐lakes approach.…”
Section: Discussionmentioning
confidence: 99%
“…However, some of our models did show a significant (negative) relationship with macrophyte cover at lake scale: total fish abundance, roach abundance as well as the abundance and biomass of fish <10 cm. Studies conducted in multiple northern temperate lakes found that excessive plant growth in a lake could reduce fish growth and the abundance of some species (Cheruvelil et al, 2005; Maceina et al, 1991; Unmuth et al, 2001). In addition, our results revealed that the negative relationships between macrophytes and total fish abundance as well as the abundance and biomass of fish <10 cm were strongly associated with lakes with high plant cover, as shown by the within‐lakes approach.…”
Section: Discussionmentioning
confidence: 99%
“…macroinvertebrates) [41], while others escaped into the upper sections of rivers (e.g. fish) [29]. In addition, most works discussed the type of maintenance works collectively and this made it difficult to determine their specific impact on the aquatic environment [12,42,43].…”
Section: Discussionmentioning
confidence: 99%
“…As noted Lusardi et al [28] in small rivers with submerged macrophytes, removal has been shown to instantly reduce macroinvertebrates abundance by 20 % -70 %. Macrophyte removal can be detrimental to fish populations, either directly when plants are harvested or indirectly through enhanced predation risk from larger fish [29], reduced food availability due to increased flow velocity [56] or deterioration of important spawning habitats [28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Macrophytes are structurally complex and often considered as ecosystem engineers in freshwater ecosystems due to their key functions for ecosystem structure and functions [12]. The spatial distribution of many fish species is linked to macrophytes t for foraging, shelter, spawning or as nurseries [16,28]. Shallow freshwater ecosystems with dense macrophytes are, however, under increasing anthropogenic pressure as macrophytes are often perceived a nuisance when interfering with human activities such as fishing, boating and swimming [30] and thus frequently removed.…”
Section: Introductionmentioning
confidence: 99%